Drying kinetics of black grapes treated with different solutions - Doymaz, I (ELSEVIER SCI LTD, 2006)
The thin-layer drying behaviour of black grapes in a laboratory dryer was examined. Various pre-treatments were applied to black grapes, which were dried at 60 degrees C with an air velocity of 1.1 m/s. The shortest drying time (25 h) was obtained with black grapes dipped in ethyl oleate plus potassium carbonate solution. Different thin-layer drying models such as Lewis, Page, Henderson and Pabis, and Two-term exponential models analysed the moisture variation of black grapes, which untreated/pre-treated with various solutions. All the models were compared according to two statistical parameter, i.e. coefficient of determination (R-2) and reduced chi-square (chi(2)). The Page model was found to be the most suitable for describing drying curves of black grapes. The effective moisture diffusivity varied from 3.82 x 10-(10) to 1.28 x 10(-9) m(2)/s. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: black grape; drying; pre-treatment solutions; thin-layer drying models; SEEDLESS GRAPES; ETHYL OLEATE; SUN; PRETREATMENTS; RAISINS; SLICES; APRICOTS; MODELS; FRUITS; Engineering; Food Science & Technology